2016
DOI: 10.1027/1864-9335/a000281
|View full text |Cite
|
Sign up to set email alerts
|

This Only Happens to Others

Abstract: Abstract. This paper investigates the specific self-presentational situations in which people confirm or negate their comparative optimism in order to convey a favorable self-image. One pilot study and three experiments showed that people increase their comparative optimism to convey an image of competence, but not one of warmth (Pilot Study, Study 1), as well as to present an advantageous self-image in professional situations, although not in friendship situations (Studies 2–3). These effects occur in self-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
0
5
0
4
Order By: Relevance
“…Participants were asked to imagine being in a job interview. Whereas such settings might particularly evoke the goal to appear competent (Le Barbenchon et al, 2016), the audience likely still values warmth also in professional contexts (Cann, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were asked to imagine being in a job interview. Whereas such settings might particularly evoke the goal to appear competent (Le Barbenchon et al, 2016), the audience likely still values warmth also in professional contexts (Cann, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Building on these findings, three experiments explore to which causes people attribute their successes in impression management situations. In these experiments, people imagine themselves in a job interview (Experiments 1 and 3) versus on a date (Experiment 2) to elicit self-presentational goals (Le Barbenchon, Milhabet, & Bry, 2016). I then test whether people's attributions of success to effort versus talent are calibrated toward the preferences of their audience.…”
Section: The Current Researchmentioning
confidence: 99%
“…The model includes a first path coefficient, a, which relates the independent variable to the mediator, and a second path coefficient, b, which relates the mediator to the dependent variable and is adjusted for the independent variable (MacKinnon, Fairchild, & Fritz, 2007). A review of the literature (e.g., Cohen et al, 2016;Le Barbenchon et al, 2016;Murayama & Elliot, 2012) leads us to expect .26 < a < .39 and .39 < b < .59. Fritz and MacKinnon (2007) call these effect sizes HM.…”
Section: Participants and Designmentioning
confidence: 99%
“…Furthermore, people exhibited CO when asked to present a favourable self-image (Tyler & Rosier, 2009), especially when wanting to convey a favourable self-image of competence (Hoorens et al, 2017; Le Barbenchon, Milhabet, & Bry, 2016). Le Barbenchon, Milhabet, Steiner, and Priolo (2008) found that people exhibiting strong CO in the context of professional fields were more highly regarded than those who exhibited low CO. People who expressed optimism or CO were generally perceived as people who take risks, undertake new projects in professional fields (Helweg-Larsen et al, 2002; Milhabet, Le Barbenchon, Cambon, & Molina, 2015) and assume entrepreneurial responsibilities (Ucbasaran, Flores, & Westhead, 2007; Ucbasaran et al, 2010). Accordingly, Milhabet et al (2015; see also Hoorens et al, 2017) concluded that people with strong CO were deemed socially useful (i.e., assertive, self-confident, competent and goal-oriented).…”
Section: Comparative Optimismmentioning
confidence: 99%
See 1 more Smart Citation